Metodología ASD aplicado al desarrollo del sistema de diagnóstico de servicios turísticos comunitarios de las Parroquias Rurales del Cantón Riobamba - Porras Vásconez, Erick Joaquin (2021)
Agile methodologies allow the management of tasks, resources, time and thus obtain the highest quality in software. The ASD (Adaptive Software Development) methodology provides an iterative development focused on components providing quality control and it allows to learn from mistakes. The limited quality of the community tourism offers in the rural parishes of the Riobamba canton due to the lack of knowledge of the current regulations for community tourism centers has caused several problems such as the lack of accessibility for inclusive tourism, an incorrect organization within the communities, lack of signage of their services and areas. For this reason, a computerized system was developed to conduct a diagnosis to evaluate compliance with the basic technical regulatory conditions of community tourism services by applying the agile ASD methodology. The application of the ASD methodology allowed to effectively manage the development of the system for an environment with constant changes and high participation of the parties, allowing to solve problems quickly until the completion of the system. The usability of the system was evaluated through surveys applied to expert users, obtaining 40% of the answers as agree and 60% agree, allowing to determine that the system is highly usable.